2009
DOI: 10.1002/cjg2.1351
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Interplanetary Shock and Its Consequent Geoeffectiveness

Abstract: Using 2.5 dimensional ideal magnetohydrodynamic (MHD) equations, the propagation of the interplanetary shock and its consequent geoeffectiveness are studied. The numerical results show that the heliospheric current sheet (HCS)–heliospheric plasma sheet (HPS) structure has some negative influences on the propagation of the interplanetary shock. For the shock propagating aslant the HCS, the segment on the opposite side of HCS with respect to shock nose is weaker than the other segment on the same side. The bendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…When IP shocks strike the Earth's magnetosphere, many geomagnetic perturbations are observed in the magnetosphere-ionosphere (MI) system, including magnetic field perturbations in geosynchronous orbit (Villante & Piersanti, 2011;, ultra-low frequency wave activity (C.-R. Zong et al, 2009), satellite orbital drag (Krauss et al, 2018;, ionospheric disturbances (Belakhovsky et al, 2017;Liu et al, 2023), and sudden impulse signatures observed by ground magnetometers around the world (Chao & Lepping, 1974;Russell et al, 1994;Smith et al, 2020). Therefore, understanding IP shock geoeffectiveness is of paramount importance in space weather investigations (Alves et al, 2011;Echer et al, 2004;Su et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When IP shocks strike the Earth's magnetosphere, many geomagnetic perturbations are observed in the magnetosphere-ionosphere (MI) system, including magnetic field perturbations in geosynchronous orbit (Villante & Piersanti, 2011;, ultra-low frequency wave activity (C.-R. Zong et al, 2009), satellite orbital drag (Krauss et al, 2018;, ionospheric disturbances (Belakhovsky et al, 2017;Liu et al, 2023), and sudden impulse signatures observed by ground magnetometers around the world (Chao & Lepping, 1974;Russell et al, 1994;Smith et al, 2020). Therefore, understanding IP shock geoeffectiveness is of paramount importance in space weather investigations (Alves et al, 2011;Echer et al, 2004;Su et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al., 2010; Zong et al., 2009), satellite orbital drag (Krauss et al., 2018; Oliveira & Zesta, 2019), ionospheric disturbances (Belakhovsky et al., 2017; Liu et al., 2023), and sudden impulse signatures observed by ground magnetometers around the world (Chao & Lepping, 1974; Russell et al., 1994; Smith et al., 2020). Therefore, understanding IP shock geoeffectiveness is of paramount importance in space weather investigations (Alves et al., 2011; Echer et al., 2004; Su et al., 2009).…”
Section: Introductionmentioning
confidence: 99%